A BURST‐BAUS consensus document for best practice in the conduct of scrotal exploration for suspected testicular torsion: the Finding Consensus for Orchidopexy in Torsion (FIX‐IT) study. (28th June 2022) - Clement, Keiran D.; Light, Alexander; Asif, Aqua; Chan, Vinson Wai‐Shun; Khadhouri, Sinan; Shah, Taimur T.; Banks, Frederick; Dorkin, Trevor; Driver, Christopher P.; During, Vinnie; Fraser, Nia; Johnston, Maximilian J.; et al.
Abstract : Objectives: To produce a best practice consensus guideline for the conduct of scrotal exploration for suspected testicular torsion using formal consensus methodology. Materials and Methods: A panel of 16 expert urologists, representing adult, paediatric, general and andrological urology used the RAND Corporation / University of California, Los Angeles (RAND/UCLA) Appropriateness Consensus Methodology to score a 184‐statement pre‐meeting questionnaire on the conduct of scrotal exploration for suspected testicular torsion. The collated responses were presented at a face‐to‐face online meeting and each item was rescored anonymously after a group discussion, facilitated by an independent chair with expertise in consensus methodology. Items were scored for agreement and consensus and the items scored with consensus were used to derive a set of best practice guidelines. Results: Statements scored with consensus increased from Round 1 (122/184, 66.3%) to Round 2 (149/200, 74.5%). Recommendations were generated in 10 categories: consent; assessment under anaesthetic; initial incision; intra‐operative decision making; fixation; medical photography; closure; operation note; logistics; and follow‐up after scrotal exploration. Our statements assume that the decision to operate has already been made. Key recommendations in the consent process included discussion of the possibility of orchidectomy and the possibility of subsequent infection of the affected testis or wound requiring antibiotic therapy. If after the examination under anaesthesia, the index of suspicion of testicular torsion is lower than previously thought, then the surgeon should still proceed to scrotal exploration as planned. A flow chart guiding decision making dependent on intra‐operative findings has been designed. If no torsion is present on exploration and bell clapper deformity is absent, the testis should not be fixed. When fixing a testis using sutures, a three‐ or four‐point method is acceptable and non‐absorbable sutures are preferred. Conclusions: We have produced consensus recommendations to inform best practice in the conduct of scrotal exploration for suspected testicular torsion.